Pre-operative echocardiogram in hip fracture patients with cardiac murmur- an audit - Talkhani Imtiyaz; Junejo Shahid; Kakwani Rajesh; Jettoo Prithee; Dixon Paul (Journal of Orthopaedic Surgery and Research, 2011)
Abstract Background All hip fracture patients with a cardiac murmur have an echocardiogram as a part of their preoperative work-up in our unit. We performed a retrospective audit to assess the impact of obtaining a pre-operative echocardiogram on the management of hip fracture patients. Methods All hip fracture patients (N = 349) between 01/06/08 and 01/06/09 were included in the study. 29 patients had pre-operative echocardiogram (echo group). A computer generated randomised sample of 40 patients was generated from N, 'non-echo' group. Data was obtained from medical records and the Hospital Information Support System (HISS). The groups were compared using Student's t test. Approval was obtained locally from the clinical governance department for this project. Results Age and gender distribution were similar in both groups. Indication for echo was an acute cardiac abnormality in 4 cases. 25 patients had echo for no new cardiac problem (indication being cardiac murmur in 23 patients and extensive cardiac history in 2 cases). Cardiology opinion was sought in 5 cases. No patient required cardiac surgery or balloon angioplasty preoperatively. Patients having pre-operative echo had significant delay to surgery (average 2.7 days, range 0-6 days) compared to 'non-echo' group (average 1.1 days, range 0-3 days), (p < 0.001). There was no significant difference in length of stay (p = 0.14) and mortality at 30 days (p = 0.41) between the groups. Conclusion We have developed departmental guidelines for expediting echo requests in hip fracture patients with cardiac murmur. A liaison has been established with our cardiology department to prioritise such patients on the Echocardiography waiting list, to prevent unnecessary avoidable delay. Careful patient selection for pre-operative echocardiography is important to avoid unnecessary delay to surgery.